Testimonio parcializado de los servidores públicos como prueba indebida en el procedimiento administrativo sancionador del GAD municipal de Santa Rosa - Amaya Torres, José Ali (2017)
An issue dedicated to the Ecuadorian civil servant and public servant, and specifically in the Administrative field, also aims to determine insofar as the biased testimony of public servants may prove undue evidence in the administrative procedure sanctioning the Decentralized Autonomous Governments Of Ecuador; With this background, the present work analyzes the degree of influence that provokes the relationship between boss and employee, since it becomes very common for civil servants or civil servants who simply do not share some criteria or belong to another partisan political grouping, with its Immediate head or their maximum head, and are subject to several annoyances until submitting them to administrative processes and to remove them from their functions, although in the Constitution of the Republic of Ecuador; Establishes in Art. 76.- Due process; "In any process in which rights and obligations of any order are determined, the right to due process, including basic guarantees, shall be ensured." For this reason, this investigation is based on the Administrative Summary against the municipal employee MEDARDO MAXIMO GUZMAN ROQUE, bearer of the citizenship card No. 0701135212